Impact of water filters and consumption of bottled water on fluoride intake - Tan, B.S; Razak, I.A (Universiti Kebangsaan Malaysia, 2013)
The objectives of this study were to assess the intake of fluoride among 4-5 years old children from drinking water (FH20) and whether current practises of use of water filters and consumption of bottled water have any impact on fluoride intake. A questionnaire survey was conducted to elicit details of drinking water in 350 children aged 4-5 years old. The intake of fluoride from drinking water over a period of two days was biochemically determined in a subsample of 200 subjects. The majority of children (97.0%) had access to tap water, 23.1% to filtered tap water and 11.3% reported use of bottled water. The use of filters was found to be associated with ethnicity and socio-economic status (p<0.00). The mean fluoride concentration of unfiltered and filtered tap water were 0.541 ± 0.167 and 0.534±0.192 ppm, respectively. The mean volume of water consumed was 1348.76±482.70 mL/day while the mean FH2O was 726.7 ± 357.5 ug/day. The use of filters and consumption of bottled water were sparse with no significant impact on FH2O over a two-day study period.